SICKLE CELL DISEASE AFFECTS PHYSICAL GROWTH - R. A. NANDANWAR; N. Y. KAMDI (International Journal of Pharma and Bio Sciences, 2013)
Anthropometric measurements were used to study the physical growth of 294 sickle cell disease(SS) children and compared with 180 normal(AA) children from the Nagpur district of Maharashtra. Both sickle cell disease male and female children were shown to have statistically significant lower weights, heights, sitting heights, hand length, foot length, interacromial diameter and intercristal diameter as compared to normal children with comparable sex and ages. This study concluded that the growth of sickle cell disease children was definitely affected by the disease process. Children with sickle cell disease were shorter, weigh less,, and had less transverse diameters.